The Place of Forensic Biology Examination within Forensic Expert Practice - Dauletyarov Д.А.; Bissenova М.К.; Salaev Н.С. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
The article discusses a general analysis of regulatory legal acts and scientific literature that establishes the specifics of legal and methodological support for conducting forensic biological examination. This includes the use of forensic biological expertise in the detection of offenses related to animal cruelty, illegal hunting, the detection of crimes and the study of factual data determined in connection with the scene of the incident during the investigation. The criteria for the forms and limits of the use of special expertise of forensic experts are also defined. The development of modern science makes it possible to significantly expand the range of objects used in the field of forensic biological research. However, this requires a revision and formation of the theoretical foundations of forensic biological examination. In line with current trends in scientific development, the range of objects used in forensic examination has expanded. This includes enabling the identification of objects of plant and animal origin. Methods for organizing forensic biological examinations were identified. The expert results obtained were comprehensively reviewed, and an in-depth analysis of the collected data was carried out. In addition, the significance of the examination and possible ways for its improvement were proposed. During the study, the scientific validity of the methods used in forensic examination was clarified. The results were analyzed as a key tool that enhances the evidentiary value and reliability of forensic biological examination and strengthens the legal substance of forensic decisions. The practical significance lies in the analysis of the results of applying methods and tools in forensic biological examinations involving animal-derived objects as a type of forensic biological expertise. The aim of the study is to analyze the theoretical and scientific-methodological foundations of forensic expert activities related to protected species of plants and animals.